The interrelationships between bank profitability, bank stability and loan growth in Southeast Asia - Dat T Nguyen; Tu DQ Le (Cogent Business & Management, 2022)
The purpose of this study is to examine the relationship between bank profitability, bank stability, and loan growth may exist in Southeast Asia, including a sample of 79 listed banks in five countries in Southeast Asia (ASEAN-5) from 2006 to 2019. Using a simultaneous equations model (SEM) with the generalized method of moments is used to examine the links bank profitability, bank stability and loan growth. The findings show a two-]way relationship between these variables. More specifically, bank profitability and stability are positively related. Bank stability and loan growth are inversely connected. Furthermore, the findings demonstrate that bank profitability and loan growth are positively related. These findings, however, suggest a trade-off in banks' pursuit of large loan growth. Our findings, however, have implications for bank supervisors, policymakers, and bank managers.
Keywords: 650; SEM; profitability; Bank stability; loan growth; Southeast Asia